2019
DOI: 10.1002/acp.3579
|View full text |Cite
|
Sign up to set email alerts
|

Non‐blind lineup administration biases administrators' interpretations of ambiguous witness statements and their perceptions of the witness

Abstract: SummaryAdministering lineups “blind”—whereby the administrator does not know the identity of the suspect—is considered part of best practices for lineups. The current study tests whether non‐blind lineup administrators would evaluate ambiguous eyewitness statements, and the witness himself or herself, in a manner consistent with their beliefs. College students (n = 219) were told the identity of the suspect or not before administering a lineup to a confederate‐witness who made an ambiguous response (e.g., “it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…Although our findings suggest that even a summary statement of witnesses’ confidence can be useful for discerning eyewitness accuracy, it is essential that the summary statement represent a faithful record of the witness’s confidence and not a subjective interpretation biased by a nonblind lineup administrator’s knowledge of who the suspect is. Indeed, knowledge of which lineup member is the suspect affects interpretations of ambiguous eyewitness statements during the identification procedure (Charman et al, 2019) and interpretations of witnesses’ verbal confidence statements following an identification (Grabman & Dodson, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although our findings suggest that even a summary statement of witnesses’ confidence can be useful for discerning eyewitness accuracy, it is essential that the summary statement represent a faithful record of the witness’s confidence and not a subjective interpretation biased by a nonblind lineup administrator’s knowledge of who the suspect is. Indeed, knowledge of which lineup member is the suspect affects interpretations of ambiguous eyewitness statements during the identification procedure (Charman et al, 2019) and interpretations of witnesses’ verbal confidence statements following an identification (Grabman & Dodson, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…direct research attention (cf. Charman et al, 2019;Rodriguez & Berry, 2014). The present study contributes to our understanding of these potential effects in two ways.…”
Section: Discussionmentioning
confidence: 71%
“…We do not yet know how generalizable the administrator blindness effects observed here and in prior studies (Charman et al, 2019;Rodriguez & Berry, 2014) are to the criminal justice system. Nonetheless, these results fit with trends observed in more ecologically valid (though less internally valid) investigations (e.g., Behrman & Davey, 2001), and suggest that the present paradigm and effects capture critical elements of how eyewitness identification evidence is preserved.…”
Section: Implications For the Use Of Eyewitness Evidencementioning
confidence: 62%
“…In the two previous experiments, we found that warning about confidence-accuracy conflation dampens the featural justification effect. In this experiment, we address the effectiveness of the warning when: (a) a different manipulation influences perceptions of certainty (prior knowledge of the police suspect; Charman et al, 2019; Grabman & Dodson, 2019), (b) effect sizes are larger than those seen in the featural justification effect, and (c) participants exhibit both a downward (i.e., ratings lower than baseline) and upward (i.e., ratings higher than baseline) contextual bias.…”
Section: Methodsmentioning
confidence: 99%